Beginning AutoCAD 2020 : exercise workbook - Shrock, Cheryl R.; Heather, Steve (Industrial Press, Inc., 2019)
For more than two decades, the Beginning AutoCAD® Exercise Workbook has been THE definitive tutorial for those learning and teaching about the CAD software. And as the AutoCAD package has continued to improve, so has this work, with better graphics, enhanced standard features (such as "CAD Tips" and side-by-side inch/metric measurements), and additional practical exercises. AutoCAD 2020 is packed with new features. The Exercise Workbook shows users and instructors how to unleash the power of AutoCAD with easy-to-follow lessons and tutorials on the many tools and commands available to create, t